Diagnosis of Jejuno-ileal Atresia vs. Malrotationassociated Midgut Volvulus in Neonates - Ovamelia Julio; Irene Lokananta; Hing Theddy (PT Kalbe Farma Tbk., 2021)
Background. In developing countries, diagnosis and treatment of congenital anomaly in neonates is quite challenging due to limited facilities and resources. Case. A 3 day-old male neonates with clinical presentation of small bowel obstruction and suspected jejuno-ileal atresia in plain abdominal radiograph. Volvulus-associated congenital malrotation with gangrenous intestines was found during surgical exploration. Resection was performed and Bishop-Koop procedure was done. Patient’s condition was deteriorated and succumbed to sepsis on day-three post-operative. Conclusion. This case illustrates potential pitfalls in clinical presentation and interpretation of plain abdominal radiographs that may negatively impact the management of neonatal obstructive ileus. Latar Belakang. Diagnosis dan tatalaksana kelainan kongenital pada neonatus di beberapa negara berkembang cukup sulit karena keterbatasan fasilitas dan sumber daya. Kasus. Neonatus laki-laki berusia 3 hari dengan gejala klinis obstruksi usus halus dan gambaran foto polos abdomen mengarah pada atresia jejunoileal. Intraoperatif dijumpai volvulus disebabkan malrotasi kongenital disertai gangren usus. Dilakukan reseksi usus dan prosedur Bishop-Koop. Kondisi pasien memburuk dan meninggal karena sepsis pada hari ketiga post-operasi. Simpulan. Kasus ini menggambarkan beberapa potensi pitfalls dalam interpretasi gejala klinis dan foto polos abdomen yang dapat berdampak negatif pada penanganan.